Fallacies of Corporate Analysis. Issue 3 (3rd May 2020) - Ellerman, David
Abstract: Corporations have been getting a bad rap lately. Many blame "corporations" for a litany of ills that, upon closer examination, should be blamed on other institutions. Our goal is to analyze a miscellany of fallacies concerning the Citizens United case, corporate personhood, the stakeholder theory, the affected interests principle, and finally ending with the deeper fallacies concerning the rights of capital that are embedded in the conventional economic theories of capital and corporate finance. In the last analysis, there is another institution that arguably is more at the root of the problems in the current economic system.